Evaluasi Strategi Terhadap Kinerja KSPPS BMT Damai Amanah Sejahtera Menggunakan Metode Servo Analysis - Ariadin Nurfi; Zahra Kamila; Siti Maesaroh; Yoiz Shofwa Shafrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to evaluate the strategy used by KSPPS BMT Damai Amanah Sejahtera on its performance using the SERVO Analysis method, which is a method that looks at five main aspects such as strategy, environment, resources, values, and organization. KSPPS BMT Damai Amanah Sejahtera is a sharia cooperative that plays an important role in empowering the community's economy, but faces various challenges in improving performance and competitiveness. This study is a case study that shows how the characteristics of this Cooperative relate to the problems faced. The results show that the SERVO method helps cooperatives understand internal and external conditions as a whole and formulate more appropriate strategies. Strategies formulated based on the results of the analysis have been shown to improve decision making and organizational performance. These findings support the theory of strategic management based on organizational resources and values, especially in the context of sharia cooperatives.